Evaluation of the efficacy of a savarnakaraka drug used in post-operative procedures of vrana treatment - Dissanayake, D.P.A. (SDM College of Ayurveda, Udupi, 2007)
According to Ayurveda health is not merely considered to be a state of freedom from ailments or disease, but rather state ...